Short- and Long-Term Relations among Prices of the Mexican Crude Oil Blend, West Texas Intermediate, and Brent: Market Trend and Risk Premia, 2005-2016 - DomÃnguez-Gijón, Rosa MarÃa; Venegas-MartÃnez, Francisco; Palafox-Roca, Alfredo Omar (International Journal of Energy Economics and Policy, 2018)
This paper uses a Vector Error Correction Model (VECM) to obtain the decomposition in permanent and transient components of prices of the Mexican Crude Oil Blend, the West Texas Intermediate (WTI) oil, and the Brent oil of the North Sea. Moreover, Granger causality tests, impulse-response analysis, and variance decomposition are carried out. The main findings are: 1) there are long-term relationships among these oil prices, 2) Brent oil mainly sets the market trend for the Mexican Crude Oil Blend, and 3) the yield-risk analysis shows that the Mexican crude oil blend offers the highest average yield and Brent provides the highest average risk premium. Keywords: Oil prices; econometric modeling, yield-risk analysis JEL Classifications: Q41, C51, G83